Antifouling microfiltration membranes prepared from poly(vinylidene fluoride)‐graft‐Poly(N‐ vinyl pyrrolidone) powders synthesized via pre‐irradiation induced graft polymerization. Issue 6 (16th October 2012) - Chen, Lifang; Hou, Zhengchi; Lu, Xiaofeng; Chen, Peng; Liu, Zhongying; Shen, Liguo; Bian, Xiaokai; Qin, Qiang
Abstract Poly(vinylidene fluoride) (PVDF) powders were grafted with N‐vinyl pyrrolidone using the pre‐irradiation induced graft polymerization technique. The effects of reaction time, absorbed dose, and monomer concentration on the degree of grafting were investigated, and the grafted PVDF powders were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, and differential scanning calorimetry. The grafted PVDF powders were also cast into microfiltration (MF) membranes via the phase‐inversion method. The contact angle and water uptake were measured. The membrane morphology was studied by scanning electron microscopy, and the water filtration properties of the membranes were tested. The antifouling properties were determined through measurements of the recovery percentage of pure water flux after the MF membranes were fouled with bovine serum albumin solution. The results confirmed that the existence of poly(N‐vinyl pyrrolidone) (PVP) graft chains improved the hydrophilicity and antifouling properties of the MF membranes cast from PVDF‐g‐PVP powders. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013